1987
DOI: 10.1084/jem.165.5.1296
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype, specificity, and function of T cell subsets and T cell interactions involved in skin allograft rejection.

Abstract: In the present study we used an adoptive transfer model with athymic nude mice to characterize the T cells involved in initiating and mediating skin allograft rejection. It was found that skin allograft rejection in nude mice required the transfer of immunocompetent T cells and that such reconstitution did not itself stimulate the appearance of T cells derived from the nude host. Reconstitution with isolated populations of Lyt-2+/L3T4- T cells resulted in the rapid rejection of MHC class I-disparate skin allog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
77
1
5

Year Published

1987
1987
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(93 citation statements)
references
References 46 publications
10
77
1
5
Order By: Relevance
“…Cytolysis of donor cells, resulting from the direct recognition of allogeneic MHC class I molecules by CD8 ϩ T cells, is thought to be the effector mechanism of rejection in different models of transplantation (4,9,10). Here, we determined whether the direct activation of CD8 ϩ T cells was required for corneal graft rejection.…”
Section: Direct Recognition Of Allogeneic Mhc Class I Molecules Is Nomentioning
confidence: 99%
See 2 more Smart Citations
“…Cytolysis of donor cells, resulting from the direct recognition of allogeneic MHC class I molecules by CD8 ϩ T cells, is thought to be the effector mechanism of rejection in different models of transplantation (4,9,10). Here, we determined whether the direct activation of CD8 ϩ T cells was required for corneal graft rejection.…”
Section: Direct Recognition Of Allogeneic Mhc Class I Molecules Is Nomentioning
confidence: 99%
“…Initial studies using reconstituted nude mice have supported the view that collaboration between helper and effector functional T cell subsets is required to ensure rejection. Either CD4 ϩ or CD8 ϩ T cells could mediate these functions (4). In several models CD4 ϩ T cells have been shown to be necessary and sufficient for the initiation of allograft rejection (5)(6)(7).…”
Section: R Ecognition By Recipient T Lymphocytes Of Alloantigens Exprmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Activation, differentiation, and expansion of naive CD8 ϩ T cells into effector cells after transplantation requires T-cell receptor/class I major histocompatibility complex interactions in conjunction with helper signals provided by CD4 ϩ T cells. 6 The importance of CD4 help is highlighted by findings in mice that CD4-cell depletion or genetic deficiency impairs the priming of donor-reactive CD8 ϩ T cells and markedly prolongs cardiac allograft survival.…”
mentioning
confidence: 99%
“…Thus, fewer studies have focused on the CD4 + T cell help requirement for the primary CD8 + T cell response. While majority of these suggested no impairment of CD8 + T cell priming in the absence of CD4 + T cell help [6,7,[14][15][16]], a few studies using primarily non-inflammatory stimuli suggested that CD4 + T cell help was absolutely or partially required for the generation a primary CD8 + T cell response [17][18][19][20][21]. Examples of the help-dependent model systems include immunization with peptide-pulsed wild-type DC injected into MHC class II-deficient mice or MHC class II-negative DC injected into normal mice [20], and immunization of CD4 -/-mice with Listeria monocytogenes secreting chicken ovalbumin [21].…”
mentioning
confidence: 99%